CR-39 في قياس تأثير النيوترونات السريعة على كاشف FTIR ومطيافية UV-Visible استخدام تقنيتي مطيافية - الجبوري, حسين علي; توفيق, ندى فاضل; زغير, عمار عبد الستار (Al-Nahrain Journal of Science, 2018)
CR-39 detector was exposure to fast neuron by Am-Ba source with neutron flux (5105 n/cm2. sec) and neutron fluence values (4.3, 8.64, 21.61010 n/cm2). Fast neutron effect on CR-39 detectors was measurement by using of using of Fourier Transform Infrared- FTIR and UV-visible spectroscopy within optical absorption– A and relative transmission percent –T% respectively.CR-39 exposure to fast neutron increase to optical absorption –A and decrease to transmission percent –T% at the wavelength range (250-290 nm) and wave number range (2000-2600 cm-1) respectively. In this study obtained there was easy to use CR-39 detectors to determination the fast neutron effect at the fluence value which is greater than 51010 n/cm2 and may be concentrated on the fast neutron effect measurement which is less than this value in the next studies.